Composite current collector and preparation method thereof, pole piece, battery and electric equipment
By using transfer technology to form the bonding layer and the metal conductive layer in lithium-ion batteries, the problem of difficult to take into account the safety and fast charging performance of lithium-ion batteries in abnormal situations is solved, and a metal conductive layer with relatively thick thickness is achieved and high efficiency is achieved. battery performance.
Patent Information
- Application Number
- CN202310693544.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-13
AI Technical Summary
Existing lithium-ion batteries are prone to ignition and explosion in abnormal situations, and the fast charging performance and safety performance are difficult to take into account. In particular, the high-temperature evaporation process has a great impact on the strength and stability of the polymer base film, resulting in conductive performance and safety. Performance degraded.
Transfer technology is used to form an adhesive layer on the polymer base film, and a metal conductive layer is formed on the adhesive layer through transfer, avoiding high-temperature evaporation process, and improving the bonding strength and conductivity of the metal conductive layer and the polymer base film. .
The battery safety and fast charging performance are achieved, and a metal conductive layer with a relatively thick thickness is obtained, which improves the needle penetration pass rate and safety performance of the battery, while reducing the impact of high temperature on the polymer base film.
Smart Images

Figure CN119133460A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of batteries, and specifically relates to a composite current collector and a preparation method thereof, a pole piece, a battery and an electrical device. Background Art
[0002] Lithium-ion batteries are widely used in electric vehicles and consumer electronics due to their high energy density, high output power, long cycle life and low environmental pollution. They are an important choice for energy storage. With the rapid development of portable electronic devices, electric vehicles and other products, the requirements for lithium-ion batteries are getting higher and higher, such as lightweight, safety performance, fast charging performance, etc. Summary of the invention
[0003] In one aspect of the present application, the present application proposes a composite current collector. The composite current collector comprises: a polymer base film; an adhesive layer, the adhesive layer being disposed on at least one side of the polymer base film; a metal conductive layer, the metal conductive layer being disposed on a side of the adhesive layer away from the polymer base film, wherein the metal conductive layer is formed on the adhesive layer by transfer. As a result, the composite current collector can not only improve the safety of the battery, but also easily obtain a thicker metal conductive layer, thereby improving the fast charging performance.
[0004] In another aspect of the present application, the present application proposes a method for preparing a composite current collector. The method comprises: forming an adhesive layer on at least one side of a polymer base film; forming a metal conductive layer on the surface of a carrier film; pressing the carrier film and the polymer base film together so that the metal conductive layer is connected to the adhesive layer; and removing the carrier film. As a result, the method is not only simple in process and does not require high-temperature evaporation of the polymer base film, but can effectively avoid or reduce the damage to the molecular structure of the polymer base film caused by high temperature conditions, and is also conducive to increasing the thickness of the metal conductive layer, thereby helping to balance the fast charging performance and safety performance of the battery.
[0005] In another aspect of the present application, the present application proposes a pole piece. The pole piece includes: the composite current collector described above, or the composite current collector prepared by the method described above; an active material layer, wherein the active material layer is disposed on at least one side of the composite current collector, and is located on the side of the metal conductive layer away from the polymer base film. As a result, the pole piece has all the features and advantages of the composite current collector described above and the method for preparing the composite current collector described above, which will not be repeated here. In general, the pole piece is beneficial for taking into account both the fast charging performance and the safety performance of the battery.
[0006] In another aspect of the present application, the present application proposes a battery. The battery comprises: the composite current collector described above, or the composite current collector prepared by the method described above, or the pole piece described above. Thus, the battery has all the features and advantages of the composite current collector described above, the method for preparing the composite current collector described above, and the pole piece described above, which will not be repeated here. In general, the battery has good fast charging performance and safety performance.
[0007] In another aspect of the present application, the present application proposes an electric device. The electric device comprises: the battery described above. The electric device has all the features and advantages of the battery described above, which will not be repeated here. In general, the electric device has a fast charging speed and good safety performance.
[0008] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0010] Figure 1 It is a schematic diagram of the cross-sectional structure of a composite current collector along its thickness direction according to an embodiment of the present application.
[0011] Figure 2 It is a schematic diagram of the cross-sectional structure of a composite current collector along its thickness direction according to another embodiment of the present application.
[0012] Figure 3 It is a flow chart of a method for preparing a composite current collector according to one embodiment of the present application.
[0013] Figure 4 It is a flow chart of a method for preparing a composite current collector according to one embodiment of the present application.
[0014] Figure 5 This is a flow chart of a method for preparing a composite current collector according to another embodiment of the present application.
[0015] Description of reference numerals:
[0016] 100-composite current collector; 20-metal conductive layer; 30-polymer base film; 40-adhesive layer; 50-carrier film; 60-release layer. DETAILED DESCRIPTION
[0017] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.
[0018] In one aspect of the present application, the present application proposes a composite current collector. According to an embodiment of the present application, reference Figure 1 It is understood that the composite current collector 100 includes: a polymer base film 30, an adhesive layer 40 and a metal conductive layer 20, wherein the adhesive layer 40 is disposed on at least one side of the polymer base film 30; the metal conductive layer 20 is disposed on the side of the adhesive layer 40 away from the polymer base film 30, wherein the metal conductive layer 20 is formed on the adhesive layer 40 by transfer. Thus, the composite current collector can not only improve the safety of the battery, but also easily obtain a thicker metal conductive layer, thereby improving the fast charging performance.
[0019] At present, the safety of batteries is an important issue that needs to be considered in their application process. Taking lithium-ion batteries as an example, they are prone to fire and explosion when subjected to abnormal conditions such as squeezing, collision or puncture, causing serious harm, which greatly limits the application and popularization of lithium-ion batteries. A large number of experimental results show that internal short circuit of the battery is the root cause of the safety hazard of ion batteries. When a short circuit occurs inside the battery due to abnormal conditions such as collision, extrusion, puncture, etc., the battery temperature will rise. In order to avoid combustion, explosion, etc. caused by excessive battery temperature, improvements are usually made in the battery diaphragm structure, battery mechanical structure, or current collector design. For example, it is proposed to introduce a low-melting point alloy into the metal current collector. As the battery temperature rises, the low-melting point alloy in the current collector melts, thereby causing the pole piece to be short-circuited, thereby cutting off the current and improving the safety performance of the battery. For another example, it is proposed to prepare a composite current collector with a multi-layer structure by composite metal layers on both sides of the resin layer. When the internal temperature of the battery rises and reaches the melting point of the resin layer material, the resin layer in the current collector melts and breaks the pole piece, thereby cutting off the power supply, improving the safety performance of the battery and increasing the battery's needle puncture pass rate.
[0020] For composite current collectors, the evaporation process is generally used to heat the coating material (or film material, such as metal, etc.) to vaporize it, and the particles of the coating material fly to the surface of the substrate and condense into a film. The physical process includes: the coating material evaporates or sublimates into gaseous particles → the gaseous particles are quickly transported from the evaporation source to the surface of the substrate → the gaseous particles attach to the surface of the substrate to nucleate and grow to form a solid film → the film atoms are reconstructed or chemically bonded. Although this method is simple to form a film, the film purity and density are high, and the film structure and performance are unique, it can be widely used in the fields of optical films, thermal protective coatings, and food / drug packaging. However, the inventors of the present application have discovered that if a metal conductive layer of a certain thickness is directly prepared on the polymer base film by an evaporation process to replace the conductive properties of a pure metal current collector, a more suitable coating thickness range needs to be achieved to meet the requirements of stable conductive properties. Directly evaporating a metal coating of a certain thickness on the polymer film not only makes the coating easy to fall off, affecting the conductive properties and square resistance of the current collector, but also affects the supporting strength and stability of the polymer base film during high-temperature heating, thereby reducing the safety performance of the battery. Furthermore, in order to meet the needs of fast charging, it is expected to further reduce the square resistance of the composite current collector, which requires plating more and thicker gold on the surface of the polymer base film. Metal layer, and the coating thickness obtained by the evaporation process is relatively thin (such as the single evaporation thickness of electron beam heating evaporation is 100-3000nm, and the single evaporation thickness of resistance heating evaporation is 10-100nm). At the same time, it is difficult to obtain a thicker metal conductive layer in a single time due to the material and thickness of the polymer base film. In order to increase the thickness of the conductive layer, if multiple evaporation methods are used, the strength and other properties of the polymer base film will decrease significantly as the number of times increases, thereby reducing the safety performance of the battery; at the same time, due to the limited thickness of the polymer base film in the composite current collector, the thickness of the metal conductive layer cannot be increased indefinitely, which hinders the manufacture of the fast-charging composite current collector.
[0021] Based on the above problems, the inventors of the present application found that a thicker metal conductive layer can be obtained on a polymer base film by transfer, and an adhesive layer can be used to improve the transfer effect and the bonding strength between the metal conductive layer and the polymer base film. For the polymer base film 30 in the present application, by forming an adhesive layer 40 on at least one side of the polymer base film 30, and then forming a metal conductive layer 20 on the side of the adhesive layer 40 away from the polymer base film 30 by transfer printing, on the one hand, the adhesive layer 40 can be used to improve the bonding strength between the metal conductive layer 20 and the polymer base film 30, avoid or reduce the risk of the metal conductive layer 20 falling off and affecting the conductive performance and square resistance of the composite current collector 100, and improve the transfer effect; on the other hand, the metal conductive layer 20 is formed on the adhesive layer 40 by transfer printing, not only does not need to use a high-temperature evaporation process for the polymer base film, but it can effectively avoid the influence of high temperature conditions on the mechanical strength of the polymer base film and the stability of the combination with the adhesive layer, which is beneficial to improve the needle puncture pass rate and safety performance of the battery, and the preparation of the metal conductive layer by transfer printing is also beneficial to increase the thickness of the metal conductive layer, thereby improving the conductive performance of the current collector, and then improving the fast charging performance of the battery. In general, the composite current collector is conducive to taking into account both the fast charging performance and safety performance of the battery. The composite current collector can improve battery safety while obtaining a thicker metal conductive layer, thereby improving fast charging performance. It is understood that the transfer process can be achieved with the aid of a carrier film, by forming a metal conductive layer of a desired thickness on the carrier film, and then transferring the metal conductive layer to the adhesive layer located on the polymer base film.
[0022] According to the embodiments of the present application, reference Figure 1 It is understood that the thickness of the polymer base film 30 can be 1μm to 20μm, for example, 1μm, 3μm, 5μm, 10μm, 15μm or 18μm, etc. The inventors found that if the thickness of the polymer base film is too small, it is difficult to provide sufficient support for the metal conductive layer 20, which is easy to limit the increase in the thickness of the metal layer, which is not conducive to improving the conductivity of the composite current collector and the fast charging performance of the battery; if the thickness of the polymer base film is too large, on the one hand, it will increase the cost of raw materials and produce unnecessary waste. On the other hand, it will also increase the thickness of the current collector, which will have a certain impact on the energy density of the battery, which is not conducive to promoting the development trend of miniaturization and lightweight of the battery. The present application controls the thickness of the polymer base film to the above range, which is more conducive to taking into account the stability of the composite current collector and the safety performance and energy density of the battery.
[0023] According to the embodiments of the present application, reference Figure 1It is understood that the thickness of the bonding layer 40 can be 1nm to 2μm, for example, 5nm, 30nm, 50nm, 100nm, 150nm, 200nm, 300nm, 500nm, 800nm, 1μm, 1.5μm or 1.8μm, etc. Increasing the thickness of the bonding layer is not only beneficial to improving the bonding force between the metal conductive layer 20 and the polymer base film 30, reducing the risk of the metal layer conductive layer falling off, but also beneficial to improving the transfer effect; however, if the thickness of the bonding layer 40 is too large, it is easy to increase the thickness of the current collector, which has a certain impact on the energy density of the battery, and is not conducive to achieving the miniaturization and lightweight of the battery. In the present application, by controlling the thickness of the bonding layer 40 to be within the above range, the adverse effects that may be produced on the thickness of the composite current collector and the energy density of the battery can be reduced on the basis of improving the interlayer bonding stability of the composite current collector.
[0024] According to the embodiments of the present application, reference Figure 1 It is understood that the thickness of the metal conductive layer 20 can be 10nm to 1mm, for example, it can be 10nm, 100nm, 500nm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 5μm, 10μm, 50μm, 100μm, 500μm, 800μm or 1mm, etc. Increasing the thickness of the metal conductive layer is not only conducive to obtaining stable conductive properties, so that the composite current collector can better replace metal foil, but also improves the fast charging performance; however, if the thickness of the metal conductive layer 20 is too large, it will not only increase the raw material cost, but also may affect the bonding strength between the metal conductive layer and the polymer base film. In the present application, by controlling the thickness of the metal conductive layer to be within the above range, it is beneficial to further take into account the structural stability and conductive properties of the composite current collector, and thus can improve the fast charging performance while improving the battery safety. Furthermore, the thickness of the metal conductive layer 20 can be selected to be 1 μm to 10 μm, for example, 1 μm, 3 μm, 5 μm, 7 μm or 9 μm, etc., so as to better balance the battery safety performance and fast charging performance. It should be noted that the material of the metal conductive layer in this application is not particularly limited, and actual personnel in this field can flexibly select it according to actual needs, for example, it can include but not limited to metal aluminum, metal copper, etc.
[0025] According to the embodiments of the present application, there is no particular restriction on the specific composition of the bonding layer 40 in the present application. Those skilled in the art can flexibly select according to the actual situation, and only need to achieve good bonding between the metal conductive layer and the polymer base film. For example, the bonding layer may include but is not limited to a bonding agent, and the bonding agent may include but is not limited to at least one of epoxy resin, aldehyde-ketone resin, polyvinyl butyral resin, polyvinylidene fluoride, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylic acid, polytetrafluoroethylene, and polyimide. For another example, the bonding layer may include a bonding agent having an active group that can react with the polymer base film, thereby further improving the bonding strength between the bonding layer and the polymer base film, thereby improving the bonding strength between the metal conductive layer and the polymer base film. For another example, the bonding layer 40 may include at least two of a bonding agent, a film former, and a coupling agent. Introducing a film former or a coupling agent in the bonding layer is also beneficial to improving the bonding strength between the metal conductive layer and the polymer base film, thereby improving the structural stability and safety performance of the composite current collector. It should be noted that there is no particular limitation on the specific types of film-forming agents and coupling agents in the present application, and those skilled in the art can flexibly select them according to actual conditions. For example, the film-forming agent may include but is not limited to at least one of alkyd resin, acrylic resin and silicone resin; the coupling agent may include but is not limited to titanate coupling agent and / or silane coupling agent.
[0026] According to some specific embodiments of the present invention, the bonding layer 40 may include: 40 to 95 parts by weight of a bonding agent, 1 to 50 parts by weight of a film former and 0.1 to 20 parts by weight of a coupling agent, for example, the amount of the bonding agent may be 50 parts by weight, 60 parts by weight, 70 parts by weight, 80 parts by weight or 90 parts by weight, etc.; the amount of the film former may be 5 parts by weight, 15 parts by weight, 25 parts by weight, 35 parts by weight, 45 parts by weight, etc.; the amount of the coupling agent may be 0.5 parts by weight, 3 parts by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight or 18 parts by weight, etc. By using the above amounts of bonding agents, film formers and coupling agents, it is more conducive to improving the bonding force between the bonding layer and the metal conductive layer and the polymer base film, thereby further improving the structural stability and safety of the composite current collector.
[0027] According to the embodiments of the present application, there is no particular restriction on the material of the polymer base film in the present application, and those skilled in the art can flexibly select it according to the actual situation. For example, the polymer base film may include but is not limited to at least one of polypropylene, polyethylene terephthalate, polyimide, polyethylene naphthalate, polytetrafluoroethylene, thermoplastic polyurethane elastomer, polypropylene, polybutylene terephthalate, polyethylene, polycarbonate, and polymethyl methacrylate. In addition, it should be noted that there is no particular restriction on the specific structure of the polymer base film in the present application. For example, the polymer base film can be a single-layer film layer formed by one or more of the above-mentioned materials, or it can include a sub-base film stacked in multiple layers. The material of each layer of the sub-base film can also be independently selected from one or more of the above-mentioned materials. As an example, the polymer base film can include one or more of biaxially oriented polypropylene film (OPP), cast polypropylene film (CPP), polyethylene terephthalate film (PET), polyimide film (PI) or polyethylene naphthalate film (PEN), polytetrafluoroethylene film (PTFE), thermoplastic polyolefin film (TPO), thermoplastic polyurethane elastomer film (TPU), polypropylene film (PP), polybutylene terephthalate film (PBT), polyethylene film (PE), polycarbonate film (PC), PMMA polymethyl methacrylate film (PMMA).
[0028] According to the embodiments of the present application, the composite current collector forms a metal conductive layer by transfer, and the thickness of the metal conductive layer can be more flexibly controlled to make the square resistance of the composite current collector lower. For example, the square resistance of the composite current collector can be less than or equal to 100mΩ / □, and specifically can be no greater than 90mΩ / □, 80mΩ / □, 70mΩ / □ or 60mΩ / □, etc., thereby being more conducive to improving the fast charging performance of the battery while meeting the battery safety performance.
[0029] Based on the same inventive concept, in another aspect of the present application, the present application proposes a method for preparing a composite current collector. Figure 3 As shown, the method includes:
[0030] 01: Forming a bonding layer on at least one side of the polymer base film
[0031] According to the embodiments of the present application, reference Figure 4It is understood that a polymer base film 30 is provided, and an adhesive layer 40 is formed on at least one side of the polymer base film 30, which is beneficial to improve the bonding force between the subsequently formed metal conductive layer 20 and the polymer base film 30, so that the composite current collector has good structural stability, and is also beneficial to improve the transfer effect in the subsequent transfer process, and facilitate the peeling of the carrier film. It should be noted that the specific method for forming the adhesive layer in this application is not particularly limited, and those skilled in the art can flexibly choose according to actual conditions, such as spraying or brushing. As a specific example, the adhesive layer raw materials including the adhesive can be dissolved in a solvent and then formed on the polymer base film by spraying or brushing. Among them, the specific composition, structure, thickness and other related features of the polymer base film and the adhesive layer have been described in detail in the previous part and will not be repeated here.
[0032] 02: Forming a metal conductive layer on the surface of the carrier film
[0033] According to the embodiments of the present application, reference Figure 4 It is understood that a carrier film 50 is provided, and a metal conductive layer 20 is formed on the surface of the carrier film 50, so as to subsequently transfer the metal conductive layer 20 to the side of the adhesive layer 40 away from the polymer base film 30. It should be noted that the specific method of forming the metal conductive layer 20 on the carrier film 50 in the present application is not particularly limited, and those skilled in the art can flexibly choose according to actual conditions, for example, evaporation, magnetron sputtering, water electroplating and the like can be used. Among them, the material, thickness and other related features of the metal conductive layer have been described in detail in the previous section and will not be repeated here. In addition, it should be noted that the order of step 01 and step 02 in the present application is not particularly limited, and those skilled in the art can flexibly adjust according to actual conditions.
[0034] According to an embodiment of the present application, the thickness of the carrier film 50 may be 1 μm to 1 mm, for example, 5 μm, 10 μm, 50 μm, 100 μm, 500 μm, 800 μm or 1 mm. Increasing the thickness of the carrier film is beneficial to improving the tensile strength of the carrier film, and is more beneficial to increasing the thickness of the metal conductive layer that can be loaded and realizing the transfer of the metal conductive layer; however, if the thickness of the carrier film is too large, it will significantly increase the size of the rotating shaft during the transfer process, which will not only increase the difficulty of the transfer operation, but also increase the volume and floor space of the equipment, and increase the cost of raw materials. The present application controls the thickness of the carrier film to be within the above range, which is beneficial to improving the effect and efficiency of the transfer. Furthermore, the tensile strength of the carrier film 50 can be greater than or equal to 1 MPa, for example, it can be 1MPa~1000MPa, 5MPa, 10MPa, 15MPa, 20MPa, 50MPa, 100MPa, etc. Controlling the tensile strength of the carrier film within the given range can avoid breakage or damage of the carrier film during the transfer operation, which affects the integrity of the metal conductive layer and is more conducive to the implementation of the transfer.
[0035] According to the embodiments of the present application, there is no particular restriction on the specific material of the carrier film in the present application, and those skilled in the art can flexibly select according to the actual situation. For example, the carrier film 50 may include a polymer film layer and / or a metal foil material, wherein the polymer film layer may include but is not limited to at least one of polypropylene, polyethylene terephthalate, polyimide, polyethylene naphthalate, polytetrafluoroethylene, thermoplastic polyurethane elastomer, polybutylene terephthalate, polyethylene, polycarbonate, and polymethyl methacrylate; the metal foil material may include but is not limited to at least one of Fe, Al, Mg, Cu, and Ni. Optionally, a metal foil material such as Al foil or Cu foil may be selected.
[0036] According to the embodiments of the present application, reference Figure 5It is understood that a release layer 60 can be first formed on the surface of the carrier film 50, and then a metal conductive layer 20 can be formed on the side of the release layer 60 away from the carrier film 50. By providing the release layer 60, it is easier to achieve the desorption of the metal conductive layer 60 from the carrier film 50 during the transfer process, thereby improving the efficiency and effect of the transfer. It should be noted that there is no particular restriction on the specific structure and composition of the release layer 60 in the present application, and those skilled in the art can flexibly select according to actual conditions. For example, the release layer can be a single-layer film layer, or it can include multiple sub-release layers stacked along the thickness direction of the carrier film; the material of the release layer can include but is not limited to at least one of ethylene-vinyl acetate copolymer, carnauba wax and refined wax. For example, when forming the release layer, at least one layer of release agent can be coated on the surface of the carrier film, and the release agent can include but is not limited to ethylene-vinyl acetate copolymer, carnauba wax and refined wax. Among them, when the release layer includes refined wax, the penetration of the refined wax can be less than or equal to 20 mm, for example, the penetration of the refined wax can be no more than 18 mm, 15 mm or 10 mm, etc., which is more conducive to reducing the release force between the metal conductive layer and the carrier film, and is beneficial to the transfer and desorption of the carrier film.
[0037] According to some specific embodiments of the present application, the release layer 60 may include 40 to 90 parts by weight of ethylene-vinyl acetate copolymer, 5 to 20 parts by weight of carnauba wax, and 1 to 10 parts by weight of refined wax. Specifically, in the release layer, the content of ethylene-vinyl acetate copolymer may be 50 parts by weight, 60 parts by weight, 70 parts by weight, or 80 parts by weight, etc.; the content of carnauba wax may be 8 parts by weight, 10 parts by weight, 15 parts by weight, or 18 parts by weight, etc.; the content of refined wax may be 2 parts by weight, 5 parts by weight, 7 parts by weight, or 9 parts by weight, etc. Thus, after the transfer is completed, it is more conducive to the desorption of the carrier film 50 and the metal conductive layer 60.
[0038] It should be noted that the specific method for forming the release layer 60 in the present application is not particularly limited, and those skilled in the art can flexibly select it according to the actual situation, for example, spraying or brushing can be used.
[0039] 03: Lamination of the carrier film and the polymer base film to connect the metal conductive layer and the adhesive layer
[0040] According to the embodiments of the present application, reference Figures 4-5 It is understood that the carrier film 50 is pressed together with the polymer base film 30 so that the metal conductive layer 20 is adhered to the adhesive layer 40 on the surface of the polymer base film 30 , thereby achieving connection between the polymer base film 30 and the metal conductive layer 20 .
[0041] According to the embodiments of the present application, the pressing pressure can be 0.1MPa to 10MPa, for example, 0.5MPa, 1MPa, 3MPa, 5MPa, 7MPa or 9MPa, etc.; and / or, the pressing temperature can be 50℃ to 500℃, for example, 60℃, 100℃, 200℃, 300℃ or 400℃, etc. The inventors found that if the pressing pressure is too small or the temperature is too low, it is easy to cause bubbles or loose fitting between the metal conductive layer and the adhesive layer, which is not conducive to the close fitting of the metal conductive layer and the adhesive layer, affecting the bonding strength of the metal conductive layer, the adhesive layer and the polymer base film, and then affecting the structural stability and use stability of the composite current collector; and if the pressing pressure is too large or the temperature is too high, it will not only increase the processing cost and generate process waste, but also easily destroy the molecular structure stability of the polymer base film when the pressing temperature is too high. The present application controls the pressing conditions to the above range, which is more conducive to improving the transfer effect and the performance stability of the composite current collector under the premise of controlling costs. Furthermore, the pressing pressure can be selected to be 1MPa~5MPa, for example, 2MPa, 3MPa or 4MPa, etc., and the pressing temperature can be 100℃~200℃, for example, 120℃, 140℃, 160℃ or 180℃, etc., which is more conducive to taking into account both the transfer effect and the stability of the polymer base film.
[0042] 04: Remove the carrier film
[0043] According to the embodiments of the present application, Figures 1-2 It is understood that after the metal conductive layer 20 is connected to the adhesive layer 40, a composite current collector including: a polymer base film 30, an adhesive layer 40 and a metal conductive layer 20 can be obtained by removing the carrier film, wherein the adhesive layer 40 is disposed on at least one side of the polymer base film 30; and the metal conductive layer 20 is disposed on a side of the adhesive layer 40 away from the polymer base film 30. The composite current collector is conducive to taking into account both the fast charging performance and the safety performance of the battery.
[0044] It can be understood that the method for preparing the composite current collector in the embodiment of the present application and the composite current collector described previously in the present application are proposed based on the same inventive concept, and all the features and advantages described for the composite current collector described previously are also applicable to the method for preparing the electronic device housing assembly, and will not be repeated here one by one.
[0045] In summary, the method for preparing the composite current collector of the above embodiment of the present application and the composite current collector described above have at least the following advantages: 1. Not only is the preparation process simple and the processing cost low, but there is no need to perform high-temperature evaporation treatment on the polymer base film, which can avoid the influence of high-temperature evaporation on the mechanical strength of the polymer and the stability of the combination with the adhesive layer, which is beneficial to improve the battery's needle penetration rate and safety performance; 2. The use of transfer printing to prepare the metal conductive layer is conducive to obtaining a thicker metal conductive layer, which is beneficial to improving the conductive properties of the current collector and improving the fast charging capability of the battery; 3. When the battery temperature rises to more than the melting point of the polymer base film due to internal short circuits and other reasons, the polymer base film will fuse and cut off the current, reducing the risk of thermal runaway. In general, the composite current collector can not only improve the safety of the battery, but also easily obtain a thicker metal conductive layer and improve the fast charging performance.
[0046] In another aspect of the present application, the present application proposes a pole piece. The pole piece includes: the composite current collector 100 mentioned above, or the composite current collector prepared by the previous method; an active material layer, the active material layer is arranged on at least one side of the composite current collector, and is located on the side of the metal conductive layer away from the polymer base film. As a result, the pole piece has all the characteristics and advantages of the composite current collector mentioned above and the method for preparing the composite current collector mentioned above, which will not be repeated here. In general, the use of the pole piece is conducive to taking into account both the fast charging performance and the safety performance of the battery. It should be noted that the specific type of the pole piece is not particularly limited, and those skilled in the art can flexibly select it according to actual needs, for example, it can be either a positive pole piece or a negative pole piece; in addition, the composition, thickness, compaction density and other characteristics of the active material layer can also be flexibly selected according to actual needs such as the type of battery and the type of pole piece, for example, conventional settings in the art can be adopted.
[0047] In another aspect of the present application, the present application proposes a battery. The battery includes: a composite current collector 100 of the aforementioned part, or a composite current collector prepared by the method of the aforementioned part, or a pole piece of the aforementioned part. Thus, the battery has all the features and advantages of the aforementioned composite current collector, the aforementioned method for preparing the composite current collector, and the aforementioned pole piece, which will not be repeated here. In general, the battery has good fast charging performance and safety performance. As a specific example, the battery includes a positive pole piece and a negative pole piece, and at least one of the positive pole piece and the negative pole piece may include the composite current collector 100 of the aforementioned part, or a composite current collector prepared by the method of the aforementioned part, or a pole piece of the aforementioned part.
[0048] It should be noted that there is no particular restriction on the specific type of battery in this application. Those skilled in the art can flexibly select according to actual conditions. For example, it can be a lithium-ion battery or a sodium-ion battery; for another example, the battery can be a cylindrical battery or a square battery; for another example, the battery can be a liquid battery or a semi-solid battery; for another example, the battery can be a battery cell, or a battery module or battery pack including battery cells. The number of battery cells in the battery module or battery pack can be flexibly selected according to its application scenario or capacity requirements. In addition, it should be noted that the battery
[0049] In another aspect of the present application, the present application proposes an electric device. The electric device comprises: the battery described above. The electric device has all the features and advantages of the battery described above, which will not be repeated here. In general, the electric device has a fast charging speed and good safety performance. It should be noted that there is no particular restriction on the specific type of electrical equipment in the present application, and those skilled in the art can flexibly choose according to actual conditions. For example, the electrical equipment may include but is not limited to portable electronic devices, wearable electronic devices, various types of computer system equipment and supporting equipment, vehicles, aircraft, household appliances, etc., and may specifically include but is not limited to mobile phones or smart phones (such as mobile phones or phone watches, etc.), mobile power supplies, e-books, electronic cigarettes, electric toothbrushes, rechargeable mice, portable game devices, laptops, PDAs, portable Internet devices, music players and data storage devices, other handheld devices and electronic devices such as watches, bracelets, wireless headphones, pendants, headphones, etc., wearable electronic devices such as massagers, electronic glasses, electronic clothes, electronic bracelets, electronic necklaces, electronic tattoos or smart watches, vehicles such as electric bicycles, electric tricycles, electric vehicles, hybrid electric vehicles, powered toy cars, aircraft such as drones, household appliances such as sweeping robots, and other products with charging requirements other than the above products, etc.
[0050] It should be noted that, in the description of this application, unless otherwise clearly specified and limited, the terms such as "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0051] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0052] Example 1
[0053] (1) coating polyvinylidene fluoride (PVDF) in N-methylpyrrolidone (NMP) solution on both sides of a biaxially oriented polypropylene film with a thickness of 5 μm to form a PVDF bonding layer with a thickness of 50 nm;
[0054] (2) A release agent is coated on the surface of a stainless steel foil having a thickness of 20 μm to form a release agent layer; a metal aluminum conductive layer having a thickness of 1 μm is formed on the surface of the release agent layer away from the stainless steel foil by a magnetron sputtering method; wherein the release agent comprises ethylene-vinyl acetate copolymer, carnauba wax and refined wax in a mass ratio of 60:10:5.
[0055] (3) laminating the copper film obtained in step (2) and the biaxially oriented polypropylene film obtained in step (1) at a laminating pressure of 3 MPa and a laminating temperature of 150° C., so that the aluminum metal conductive layer is connected to the adhesive layer;
[0056] (4) Peel off the polypropylene film to obtain a composite current collector.
[0057] Example 2
[0058] Compared with Example 1, the difference is that in step (2), the thickness of the stainless steel foil is 20 μm; and the thickness of the formed metal aluminum conductive layer is 2 μm.
[0059] Step (2) is specifically as follows: coating a release agent on the surface of a stainless steel foil having a thickness of 20 μm to form a release agent layer; forming a metal aluminum conductive layer having a thickness of 20 nm on the surface of the release agent layer away from the stainless steel foil by magnetron sputtering, and then increasing the thickness of the aluminum layer to 2 μm by multiple or single vacuum evaporation; wherein the release agent comprises ethylene-vinyl acetate copolymer, carnauba wax and refined wax in a mass ratio of 60:10:5.
[0060] Example 3
[0061] Compared with Example 2, the difference is that in step (2), the thickness of the formed metal aluminum conductive layer is 5 μm.
[0062] Example 4
[0063] Compared with Example 2, the difference is that in step (3), the pressing pressure is 0.8 MPa and the pressing temperature is 50°C.
[0064] Example 5
[0065] Compared with Example 2, the difference is that in step (3), the pressing pressure is 5 MPa and the pressing temperature is 100°C.
[0066] Comparative Example 1
[0067] The metal aluminum conductive layer is directly evaporated on both sides of a 5μm thick biaxially oriented polypropylene film using an evaporation process. The evaporation temperature is 200°C. Multiple parallel groups are used to control the evaporation time and the number of back and forth evaporation cycles of each parallel group. By comparison, the maximum thickness of the metal aluminum conductive layer that can be obtained by evaporation is 0.6μm.
[0068] Comparative Example 2
[0069] Compared with Example 2, the difference is that step (1) is not performed, and the cast polypropylene film obtained in step (2) is directly pressed with a biaxially oriented polypropylene film with a thickness of 5 μm, so that the metal aluminum conductive layer is directly bonded to the polypropylene film.
[0070] Battery assembly and testing
[0071] The composite current collectors prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were used to prepare positive and negative electrode sheets, and the battery was assembled. The specific process is as follows:
[0072] (1) Graphite, conductive carbon black, styrene-butadiene rubber, and sodium hydroxymethyl cellulose were mixed in a mass ratio of 94.5:1:2.25:2.25, the mixed powder was placed in a vacuum mixer, deionized water was added and stirred to obtain a negative electrode active slurry, the negative electrode active slurry was evenly coated on the opposite sides of the composite current collector to form a negative electrode active material layer, the negative electrode current collector coated with the negative electrode active slurry was transferred to an oven for drying, and then rolled and cut to obtain a coating surface density of 145 g / m 2 The negative electrode;
[0073] (2) Nickel-cobalt-manganese positive electrode material (NCM811), conductive agent Super-P, and binder PVDF were mixed in a mass ratio of 95:2.5:2.5, the mixed powder was placed in a vacuum mixer, N-methylpyrrolidone was added, and the mixture was stirred evenly to obtain a positive electrode active slurry, and the positive electrode active slurry was evenly coated on the opposite sides of the composite current collector to form a positive electrode active material layer, and the positive electrode current collector coated with the positive electrode slurry was transferred to an oven for drying, and then rolled and cut to obtain a coating surface density of 440 g / m 2 The positive electrode;
[0074] (3) Ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1 to obtain a mixed solution, and dry LiPF6 was added to the mixed solution to prepare an electrolyte with a concentration of 1 mol / L;
[0075] (4) A polyethylene porous membrane is used as a separator, and the positive electrode sheet, negative electrode sheet and separator are stacked in order, and then wound to obtain a bare battery cell, and the bare battery cell is placed in an aluminum-plastic film soft package, and after drying, an electrolyte is injected, and a secondary battery is obtained after vacuum packaging, standing, forming, shaping and other processes.
[0076] Analysis and testing
[0077] Under the same conditions, the square resistance of the composite current collector obtained by each embodiment and comparative example, the bonding strength of the metal conductive layer, and the fast charging performance and safety performance of the prepared battery were tested. The test results are shown in Table 1, wherein the test methods for fast charging performance and safety performance are as follows:
[0078] Bonding strength of metal conductive layer: Adhesion (100 grids) test according to international standard ISO 2409
[0079] Fast charging performance of the battery: After the first constant voltage and constant current charge and discharge at 25°C, the battery was charged at 3C and 5C rates respectively, and the time to charge to 90% of the full load was recorded.
[0080] Puncture test: The battery was subjected to a puncture test according to the test method in 6.2.8 of GB / T 31485-2015. 100 secondary battery samples were taken from each embodiment and comparative example for testing. The puncture pass rate of each embodiment and comparative example was recorded, as shown in Table 1.
[0081] Table 1 Test results of Examples 1 to 5 and Comparative Examples 1 to 2
[0082]
[0083] Results and Discussion
[0084] In summary, the composite current collector prepared by the method of the embodiment of the present application can obtain a thicker metal conductive layer, and the metal conductive layer is not easy to fall off, and the safety performance and fast charging performance are better. Among them, combined with Comparative Example 1 and Examples 1 to 5, it can be seen that compared with the metal conductive layer formed directly on the surface of the polymer substrate by the traditional evaporation process, the composite current collector with a thicker metal conductive layer can be prepared by the transfer method. For example, the maximum thickness of the metal conductive layer formed directly on the surface of the polymer substrate by the traditional evaporation process in Comparative Example 1 is only 0.6μm, which is much lower than the thickness of the metal conductive layer that can be formed by the above embodiment of the present application (such as 5μm), and the composite current collector prepared by the method of the above embodiment of the present application has better fast charging performance and higher safety performance; in addition, compared with Example 2, the bonding strength of the composite current collector obtained in Comparative Example 2 is poor, resulting in a decrease in the safety performance of the battery. The main reason is that no bonding layer is provided, resulting in a decrease in the adhesion of the metal conductive layer, which affects the safety performance to a certain extent. In summary, the composite current collector prepared by the method of the above embodiment of the present application is not only safer, but also easy to obtain a thicker metal conductive layer, which can significantly improve the fast charging performance.
[0085] In the description of the present application, the description with reference to the terms "some embodiments", "examples", "specific examples", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradicting each other.
[0086] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A composite current collector, characterized in that: include: polymer-based films; an adhesive layer disposed on at least one side of the polymer base film; a metal conductive layer, the metal conductive layer being disposed on a side of the adhesive layer away from the polymer base film, Wherein, the metal conductive layer is formed on the bonding layer by transfer.
2. The composite current collector according to claim 1, characterized in that: At least one of the following conditions is met: The thickness of the polymer base film is 1 μm to 20 μm; The thickness of the bonding layer is 1 nm to 2 μm; The thickness of the metal conductive layer is 10 nm to 1 mm, and can be optionally 1 μm to 10 μm.
3. The composite current collector according to claim 1 or 2, characterized in that: At least one of the following conditions is met: The bonding layer includes at least two of a bonding agent, a film-forming agent and a coupling agent; The polymer base film includes at least one of polypropylene, polyethylene terephthalate, polyimide, polyethylene naphthalate, polytetrafluoroethylene, thermoplastic polyurethane elastomer, polypropylene, polybutylene terephthalate, polyethylene, polycarbonate, and polymethyl methacrylate.
4. The composite current collector according to claim 3, characterized in that: At least one of the following conditions is met: The bonding layer comprises at least one of epoxy resin, aldehyde-ketone resin, polyvinyl butyral resin, polyvinylidene fluoride, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylic acid, polytetrafluoroethylene, and polyimide; The bonding layer includes a bonding agent having an active group that can react with the polymer base film; The film former includes at least one of an alkyd resin, an acrylic resin and a silicone resin; The coupling agent includes a titanate coupling agent and / or a silane coupling agent; The bonding layer comprises: 40 to 95 parts by weight of the bonding agent, 1 to 50 parts by weight of the film-forming agent, and 0.1 to 20 parts by weight of the coupling agent.
5. The composite current collector according to claim 1 or 4, characterized in that: The square resistance is less than or equal to 100mΩ / □.
6. A method for preparing a composite current collector, characterized in that: include: forming a bonding layer on at least one side of the polymer-based film; forming a metal conductive layer on the surface of the carrier film; Laminating the carrier film and the polymer base film so that the metal conductive layer is connected to the adhesive layer; The carrier film is removed.
7. The method according to claim 6, characterized in that The pressing pressure is 0.1 MPa to 10 MPa; and / or the pressing temperature is 50° C. to 500° C.
8. The method according to claim 6, characterized in that The pressing pressure is 1 MPa to 5 MPa; and / or the pressing temperature is 100° C. to 200° C.
9. The method according to claim 6, characterized in that At least one of the following conditions is met: The thickness of the carrier film is 1 μm to 1 mm; The carrier film comprises a polymer film layer and / or a metal foil; The tensile strength of the carrier film is greater than or equal to 1 MPa.
10. The method according to claim 9, characterized in that The polymer film layer includes at least one of polypropylene, polyethylene terephthalate, polyimide, polyethylene naphthalate, polytetrafluoroethylene, thermoplastic polyurethane elastomer, polybutylene terephthalate, polyethylene, polycarbonate, and polymethyl methacrylate; and / or, The metal foil includes at least one of Fe, Al, Mg, Cu and Ni.
11. The method according to any one of claims 6 to 10, characterized in that: Also includes: A release layer is formed on the surface of the carrier film, and the metal conductive layer is formed on a side of the release layer away from the carrier film.
12. The method according to claim 11, characterized in that The release layer includes a plurality of sub-release layers stacked along the thickness direction of the carrier film; and / or, The release layer includes at least one of ethylene-vinyl acetate copolymer, carnauba wax and refined wax.
13. The method according to claim 12, characterized in that The release layer comprises: 40 to 90 parts by weight of the ethylene-vinyl acetate copolymer, 5 to 20 parts by weight of the carnauba wax and 1 to 10 parts by weight of the refined wax; and / or, The needle penetration of the refined wax is less than or equal to 20 mm.
14. A pole piece, characterized in that: include: The composite current collector according to any one of claims 1 to 5, or the composite current collector is prepared by the method according to any one of claims 6 to 13; An active material layer is provided on at least one side of the composite current collector and is located on a side of the metal conductive layer away from the polymer-based film.
15. A battery, characterized in that: include: The composite current collector according to any one of claims 1 to 5; Or, the composite current collector is prepared by the method according to any one of claims 6 to 13; Or, the pole piece as described in claim 14.
16. An electrical equipment, characterized in that: include: The battery of claim 15.
Citation Information
Cited By
Current collector and method for manufacturing current collector
WO2026144305A1
